Protocol of chemical and bacteriological safety control of water for hemodialysis / haemodiafiltration - L. Snisar; L. Liksunova (Ukrainian Journal of Nephrology and Dialysis, 2018)
Conducting hemodialysis/ haemodiafiltration requires the presence of specially prepared water, which is the main component of the dialysing solution. The source of dialysis water is drinking (tap) water which is submitted to purification cascade that involves, among others, pressure driven membranes processes such as reverse osmosis (RO). Proper water treatment is not only a guarantee of the safety of the hemodialysis procedure, but also significantly affects the quality and life expectancy of patients.Therefore, the chemical and microbiological quality of the water used for dialysis is essential if an additional health risk to haemodialysis patients is to be avoided.